2012
DOI: 10.3109/00365521.2012.711853
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adalimumab for induction of endoscopic healing and normalization of mucosal cytokine gene expression in Crohn's disease

Abstract: Adalimumab induces accumulated complete endoscopic healing in 44% of patients after 52 weeks of therapy. Normalization of mucosal gene expression of cytokines does not occur in all patients with endoscopy-verified healed mucosa. Inclusion of normalized mucosal cytokine expression into the concept of mucosal healing could have an impact on long-term clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…This may demonstrate the effects of the induction therapy itself 20. A study published after EXTEND also showed mucosal healing at week 12 after adalimumab induction therapy 57. Mucosal healing, defined by CDEIS score, has been demonstrated as early as week 4 in a study with infliximab5 and as early as 10 weeks with certolizumab 58.…”
Section: Resultsmentioning
confidence: 93%
“…This may demonstrate the effects of the induction therapy itself 20. A study published after EXTEND also showed mucosal healing at week 12 after adalimumab induction therapy 57. Mucosal healing, defined by CDEIS score, has been demonstrated as early as week 4 in a study with infliximab5 and as early as 10 weeks with certolizumab 58.…”
Section: Resultsmentioning
confidence: 93%
“…It was presented that infliximab treatment (5 mg/kg, every 8 weeks for 6 months) to patients after resection of CD showed a decrease in mucosal IL-1β, IL-6 and TNF-α which contributed to the suppressive effect on clinical and endoscopic disease activity (Yamamoto et al 2009). Similarly, six injections of adalimumab to 70 CD patients (80 mg at week 0 and then 40 mg every 2 weeks as subcutaneous injections), another anti-TNF-α antibody, for 10 weeks to patients with CD significantly decreased mucosal mRNA level of TNF-α, INF-γ, IL-17A and IL-23 (Rismo et al 2012). The decreased level of IFN-γ may result from its reduced secretion by T cells and depletion of TNF levels (Agnholt and Kaltoft 2001).…”
Section: Clinical View Of the Anti-oxidative Role Of Drugs Used In Ibmentioning
confidence: 97%
“…These values have been generated by consensus among authors 54 in distinction to objective data. 53 Given the high degree of correlation between the CDEIS and the simplicity of its application, the SES-CD has gained popularity for the assessment of eligibility 55 and outcome 36,[56][57][58][59][60][61][62][63][64] in clinical trials. A modified SES-CD that only examines ulcer size and ulcerated surface area has also been reported.…”
Section: Simple Endoscopic Score In Crohn's Diseasementioning
confidence: 99%